LOWER LIMB SALVAGE FOR TUMOURS AROUND THE KNEE USING ONCOLOGICAL RESECTIONS AND MEGAPROSTHETIC RECONSTRUCTIONS - Faridullah Khan Zimri,; Saaiq, Muhammad; Muhammad Nouman,; Faisal Qayyum, (Journal of Ayub Medical College Abbottabad, 2023)
Background: This descriptive case series documented the clinical presentation of tumours around the knee in our population and explored the outcome of lower limb salvage with oncological resections and megaprosthetic reconstructions. The variables analysed included return of knee function, disease free survival and any complications observed over a follow up period of 5-years. Methods: The study spanned over a period of 13-years. It included adult patients of all genders who presented with tumours around the knee and underwent tumour resections followed by megaprosthetic reconstructions at our institute. Results: Out of 73 patients, there were 43 (58.90%) males and 30 (41.09%) females. Their ages ranged between 16-53 years with a mean of 32.97±10.68 years. The tumours included giant cell tumours (n=41), osteosarcomas (n=24), Spindle cell sarcoma (n=5), chondrosarcoma (n=2) and Ewing's sarcoma (n=1). The average postoperative musculoskeletal tumour society (MSTS) score was 84.65%. Various complications encountered included superficial infections/ delayed wound healing among 9 (12.32%) patients, local recurrence in 6 (8.21%), deep infections among 5 (6.84%) and transient palsy of peroneal nerve in 3 (4.10%) cases. There was aseptic loosening and traumatic disruption of extensor mechanism one each (1.36%). There were 7 (9.58%) mortalities in our series. Conclusion: Giant cell tumours and osteosarcomas were the most frequent tumours observed around the knee. The tumours affected relatively younger population. Safe oncological resections of the tumours followed by megaprosthetic reconstructions provided reasonable outcome in the majority of patients.